PENGARUH HUTANG JANGKA PENDEK, HUTANG JANGKA PANJANG, DAN TOTAL HUTANG TERHADAP ROA DAN ROE PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ-45 DI BEI PERIODE 2011-2014 - Jati, Akhkim Kuncoro; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the factors that affect of debt level including short-term debt, long-term debt, and total debt on firm’s performance which using ROA and ROE as a profitability measurements ratio.This study using multiple regression analysis in estimating the relationship between the debt level and firm’s performance. Object in this study are a listed company in the LQ-45 index on Indonesia Stock Exchange (IDX) and always published the financial statements and annual report for the period 2011-2014. Purposive sampling method was using to select the sample and obtained 72 samples. Data used is secondary data such as financial statements and annual reports. Analysis of the data used is descriptive statistics, the classic assumption test, and regression analysis.Based from classic assumption test, there is no found any data storage so that data has been qualified. From the regression analysis test showed that short-term debt (STD) has a significantly positive relationship with ROA, long-term debt (LTD) has asignificantly negative relationship with ROA, while total debt (TTD) has no significant on ROA. On the other hand, short-term debt (STD) and total debt (TTD) has a positively significant among ROE, while long-term debt (LTD) is negatively significant with ROE.